LA PARTE MALDITA DE LOS NUEVOS CABALLEROS DEL MUNDO - Sanabria, Fabián (Educere et Educare, 2014)
<!--[if gte mso 9]> 72 544x376 <![endif]--> Por Fabián Sanabria “I said to my soul, be still and wait without hope, For hope would be hope for the wrong thing; wait without love, For love would be love of the wrong thing; there is yet faith But the faith and the love and the hope are all in the waiting. Wait without thought, for you are not ready for thought: So the darkness shall be the light, and the stillness the dancing. Whisper of running streams, and winter lightning”. “J'ai dit à mon âme, reste immobile et attends sans espoir Car cet espoir serait un espoir mal dirigé Attends sans amour Car cet amour serait un amour pour un objet trompé Il y a encore la foi Mais la foi et l'amour et l'espoir restent tous dans l'attente Attends donc sans pensée Car tu n'es pas prêt pour la pensée Allors l'obscurité deviendra lumiére Et l'immobilité sera danse. Chuchotements des courses Et des éclairages d'hiver”. T. S Elliot, “East Coker”, from The Four Quatets. <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->